2023
DOI: 10.3390/ijms24043897
|View full text |Cite
|
Sign up to set email alerts
|

The Human Virome and Its Crosslink with Glomerulonephritis and IgA Nephropathy

Abstract: The prokaryotic, viral, fungal, and parasitic microbiome exists in a highly intricate connection with the human host. In addition to eukaryotic viruses, due to the existence of various host bacteria, phages are widely spread throughout the human body. However, it is now evident that some viral community states, as opposed to others, are indicative of health and might be linked to undesirable outcomes for the human host. Members of the virome may collaborate with the human host to retain mutualistic functions i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 125 publications
0
2
0
Order By: Relevance
“… 28 Involvement of IL-6 plays a critical role in the IgA deposition process of IgAN. 29 PKR is typically activated by both viral and bacterial RNA species. Interestingly, an independent study demonstrated that HBsAg augments the glucose/cAMP/PKR/CREB signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
“… 28 Involvement of IL-6 plays a critical role in the IgA deposition process of IgAN. 29 PKR is typically activated by both viral and bacterial RNA species. Interestingly, an independent study demonstrated that HBsAg augments the glucose/cAMP/PKR/CREB signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Viral infections are involved in a variety of glomerular diseases ( Sallustio et al, 2023 ). The gut virome, particularly the part dominated by bacteriophages, plays a crucial role in the ecological balance of gut microbiota.…”
Section: Discussionmentioning
confidence: 99%
“…Starting from the assumption that in patients with IgAN there is an alteration of the intestinal microbiota, new therapeutic strategies are emerging, such as the use of antibiotics or dietary implementation with prebiotics and/or probiotics, or FMT [66,67].…”
Section: Fecal Microbiota Transplantationmentioning
confidence: 99%